Effects of solid waste-based soil conditioner and arbuscular mycorrhizal fungi on crop productivity and heavy metal distribution in foxtail millet (Setaria italica). (1st July 2022) - Shen, Wuyan; Feng, Zhengjun; Song, Huiping; Jin, Dapeng; Fu, Yuanhong; Cheng, Fangqin
Abstract: Shanxi is a large coal-producing province, and it also produces a lot of solid waste. Solid waste can leach heavy metals, which can harm soil and affect food security at the beginning of the food chain. To investigate the impacts of solid waste-based soil conditioner (SWSC) and arbuscular mycorrhizal fungi (AMF) on millet safety and crop production, a field experiment with foxtail millet ( Setaria italica ) was conducted in Tunliu. The results of this study demonstrate that SWSC + AMF, SWSC and AMF can increase millet yield by 28.0%, 27.1% and 19.5%, respectively, compared with CK. This is mainly due to increased mycorrhizal infection. Besides, the pollution index (Pi ) and the Nemerow-integrated pollution index (PN ) of the soil with SWSC and AMF were both below 0.7, indicating safe pollution levels. The application of AMF and SWSC inhibits plants from absorbing heavy metals from the soil and reduces the TFroot/soil of the millet. SWSC + AMF application inhibited the transfer of heavy metals from the roots to the upper part of the ground and reduced the TFshoot/root of the millet. The TFgrain/soil of the millet was below 1. The HQ and HI of the millet grains did not exceed 1, indicating the absence of a potential health risk. Therefore, SWSC combined with AMF is applicable for millet production in Tunliu, and the combined treatment can decrease heavy metal phytoavailability and post-harvest transfer risks. This work provides a way to utilize solid waste while also improving millet yields in dry farming. Based on the review, we suggested future researches to better understand the mechanisms of SWSC + AMF long-term application to promote awareness on its role over time through alterations in its surface chemistry, soil microbial community and environmental implications. Graphical abstract: Image 1 Highlights: SWSC or AMF alone can increase millet yield and reduce heavy metals uptake. SWSC can adsorb heavy metals and fix them in the soil. AMF fixes heavy metals through the mycelium and reduces the TFroot/soil . Applying SWSC + AMF can better reduce the TFshoot/root of the millet.